Two Lineages of Pseudomonas aeruginosa Filamentous Phages: Structural Uniformity over Integration Preferences. (13th July 2020) - Fiedoruk, Krzysztof; Zakrzewska, Magdalena; Daniluk, Tamara; Piktel, Ewelina; Chmielewska, Sylwia; Bucki, Robert
Abstract: Pseudomonas aeruginosa filamentous (Pf) bacteriophages are important factors contributing to the pathogenicity of this opportunistic bacterium, including biofilm formation and suppression of bacterial phagocytosis by macrophages. In addition, the capacity of Pf phages to form liquid crystal structures and their high negative charge density makes them potent sequesters of cationic antibacterial agents, such as aminoglycoside antibiotics or host antimicrobial peptides. Therefore, Pf phages have been proposed as a potential biomarker for risk of antibiotic resistance development. The majority of studies describing biological functions of Pf viruses have been performed with only three of them: Pf1, Pf4, and Pf5. However, our analysis revealed that Pf phages exist as two evolutionary lineages (I and II), characterized by substantially different structural/morphogenesis properties, despite sharing the same integration sites in the host chromosomes. All aforementioned model Pf phages are members of the lineage I. Hence, it is reasonable to speculate that their interactions with P. aeruginosa and impact on its pathogenicity may be not completely extrapolated to the lineage II members. Furthermore, in order to organize the present numerical nomenclature of Pf phages, we propose a more informative approach based on the insertion sites, that is, Pf-tRNA-Gly, -Met, -Sec, -tmRNA, and -DR (direct repeats), which are fully compatible with one of five types of tyrosine integrases/recombinases XerC/D carried by these viruses. Finally, we discuss possible evolutionary mechanisms behind this division and consequences from the perspective of virus–virus, virus–bacterium, and virus–human interactions.